2020
DOI: 10.1111/aphw.12230
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to COVID‐19 Precautionary Measures: Applying the Health Belief Model and Generalised Social Beliefs to a Probability Community Sample

Abstract: Background In the face of the global pandemic of coronavirus disease‐2019 (COVID‐19), people’s adherence to precautionary behavioral measures (e.g. social distancing) largely influences the effectiveness of those measures in containing the spread of the coronavirus. The present study aims at testing the applicability of the health belief model (HBM) and generalised social beliefs (i.e. social axioms) to explore strategies for promoting adherence to COVID‐19 precautionary measures. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
165
5
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 53 publications
13
165
5
8
Order By: Relevance
“…In general, the findings have suggested that the TPB can be applied to explain social distancing behavior. TPB involves factors of individual levels (attitude and perceived behavioral control) and interpersonal levels (subjective norms), which has been commonly used in explaining protective behaviors related to emerging infectious diseases including COVID-19 [ 10 , 27 , 28 ]. It is, however, important to consider factors of community level.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the findings have suggested that the TPB can be applied to explain social distancing behavior. TPB involves factors of individual levels (attitude and perceived behavioral control) and interpersonal levels (subjective norms), which has been commonly used in explaining protective behaviors related to emerging infectious diseases including COVID-19 [ 10 , 27 , 28 ]. It is, however, important to consider factors of community level.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , the theoretical model presents the interrelationships of the constructs and panic buying behavior. The health belief model has been applied in the numerous community-based health interventions contexts [ 42 , 43 , 44 ] and its elements (i.e., perceived susceptibility, perceived severity, outcome expectancy, cues to action, and self-efficacy) explain the determinants of the perceived scarcity of products in the pandemic. This perceived scarcity subsequently leads to anticipated regret and panic buying behavior [ 52 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies reported that female students and those with the positive attitudes and knowledge towards handwashing for COVID-19 prevention were more likely to adopt handwashing behavior [ 18 , 19 ]. Further, studies utilized the theory of planned behavior, health action process approach, and health belief model to explain handwashing behavior in college students and adults during the COVID-19 pandemic [ 20 ]. Positive attitudes, positive subjective norms about handwashing behavior, higher perceived benefits of handwashing, and lower barriers to handwashing were associated with adherence to proper handwashing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies utilized the theory of planned behavior, health action process approach, and health belief model to explain handwashing behavior in college students and adults during the COVID-19 pandemic [ 20 ]. Positive attitudes, positive subjective norms about handwashing behavior, higher perceived benefits of handwashing, and lower barriers to handwashing were associated with adherence to proper handwashing [ 20 ]. Additional information on factors related to initiation and continuation of the handwashing behavior to prevent COVID-19 spread is needed to ensure greater behavior adoption rates among college students.…”
Section: Introductionmentioning
confidence: 99%